Upper Limb Rehabilitation Device with Force Control Feedback - Abd Rasid, Nur Ain; Abdul Rahman, Hisyam (Evolution in Electrical and Electronic Engineering, 2022)
Stroke is one of the most common causes of long-term disability in humans and will be undergoing a rehabilitation process where it is a long and difficult process for motor recovery. Currently, existing methods of therapy are less attractive and exhausting, which can lead patients to discontinue their therapy. The aim of this project is to introduce game-based therapy that interfaces with an  upper limb rehabilitation device. A video game is developed using the Unity Engine. The mechanical structure is based on a human arm anatomy skeleton that provides physical assistance and supports the stroke patient’s movement during their therapy since stroke patient has difficulty moving their hand. The upper limb rehabilitation exoskeleton was designed with one degree of freedom (DOF) with the range of motion (ROM) from angle 0º to 90º. The force control method can follow or imitate the resistive training motion of flexion or extension patient’s movement. Finally, the upper limb rehabilitation devices are tested with three healthy subjects. The result shows that the device is reliable for stroke patients to use for their rehabilitation therapy. The device has the potential to increase the motivation of stroke patients to continue the rehabilitation process. However, further studies need to be conducted.